Calcium signalling and breast cancer. (October 2019) - So, Choon Leng; Saunus, Jodi M.; Roberts-Thomson, Sarah J.; Monteith, Gregory R.
Abstract: The past two decades have seen the identification of important roles for calcium signalling in many of the hallmarks of cancer. One of the cancer types that has been a particular focus of such studies is breast cancer. The breast is intrinsically linked to the calcium ion due to the importance of milk calcium in neonatal growth and development. Indeed, some of the calcium channels and pumps involved in transporting calcium ions into milk also have altered expression in some breast cancers. However, altered expression is not confined to channels and pumps important in lactation, other calcium channels and pumps may also be modulated and may even be specific to breast cancer molecular subtypes. This review considers calcium signalling in the context of breast cancer and provides an overview of the roles that have been attributed to specific regulators of cellular calcium levels in processes relevant to breast cancer progression. Emerging areas in the study of calcium signalling in breast cancer are considered, such as the intersection between calcium signalling, the tumour microenvironment and breast cancer.